MANUSIA DAN HISTORISITASNYA MENURUT MARTIN HEIDEGGER - Tjahyadi, Sindung (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractHeidegger viewed âfreedomâ and âtranscendenceâ (retrospective consciousness) as the element that determines âthe way of human existenceâ and also the human understanding of âhistoryâ radically. Philosophy of history is the main point ofHeideggerâs philosophy. It is showed by his most fundamentalconcept of âtemporalityâ. Heidegger so far developed the basiccharacteristic of relationship of âBeingâ (reality) and âtimeâ(horizon) as a dialectical relationship. Because of his âpoeticânuance, Heidegger often makes someone confused for his called for âBeingâ as a âpersonâ, e.g., it as âthe giver of blessingâ. Heidegger brings to the âtrueâ understanding that all philosophical inquiries start and end in the understanding of human being.Keywords: the way of being, being, history, human being